Progress Testing and Module Final Scoring as part of Curriculum Evaluation in Faculty of Medicine Syarif Hidayatullah State Islamic University Jakarta, Indonesia - Fadhilah, Marita; Sari, Nurmila; Dwiyanti, Sophie; Suwarsono, Erike A; Ekayanti, Fika (International Journal of Human and Health Sciences (IJHHS), 2020)
Introduction: Progress testing (PT) reflects students’ knowledge development and is a valuable indicator for curriculum evaluation. Since 2009, Faculty of Medicine Syarif Hidayatullah State Islamic University Jakarta (FMSH) has been conducting PT every year as a formative assessment. In 2012, curriculum reform was addressed to revise the 2005 curriculum; until then PT and curriculum evaluation were not conducted concurrently. This study aims to evaluate PT and assess whether there is a relationship between PT performance and final scores in modules, as part of curriculum evaluation. Method: It reviews PT for two cohorts: 571 students in 2015 and 562 students in 2016. 120 systembased topics were addressed in the PT. In this study the final scores for the old (2015) and new (2016) curriculum neuropsychiatry modules are reviewed, since their scores were lower than for other modules. Comparisons were made using ANOVA. Pearson correlations were calculated to examine the relationship between PT and final module scores. Results: This study revealed that PT scores between each grade (p < 0.001) from 2015 to 2016 improved significantly (54.49 ± 7.43 and 55.07 ± 8.32; p < 0.001). The mean of the final score of the new neuropsychiatry module was 69.36 ± 3.78 while the old one was 70.92 ± 3.99. Furthermore, Pearson correlation showed a weak correlation between final scores for the neuropsychiatry module and PT scores in 2015 (ρ = 0.191, p = 0.011). Discussion: PT scores increased significantly. Despite the final score of the new neuropsychiatry module being lower than the old one, there was heterogeneity in scores within the old neuropsychiatry module. The small number of neuropsychiatry items in the PT explains why the correlation between PT and final scores was weak. The weak correlation between final scores for the neuropsychiatry module and the PT scores in 2015; PT and final module scores seem reliable as indicators of curriculum evaluation. Further study is needed to analyze more cohort PT scores and modules. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 62-68